The Making of Cinnamon Leaf Flavored Crisp - Nia Rizki Paramida; Terip Karo-Karo; Era Yusraini (Jurnal Rekayasa Pangan dan Pertanian, 2013)
The aim of this research was to find the effect of the proportion of cinnamon leaf and the mixture of rice flour with tapioca on the quality of cinnamon leaf flavored crisp. This research was using completely randomized design with two factors, i.e. : the proportion of cinnamon leaf (D) : (0%, 2%, 4%, 6% and 8%) and the mixture of rice flour and tapioca (T) : (50%:50%, 62,5%:37,5%, 75%:25% and 87,5%:12,5%). Parameters analyzed were moisture content, ash content, fiber content, fat content, organoleptic values of color, flavor, taste and crispiness. The results showed that the proportion of cinnamon leaf had highly significant effect on moisture content, ash content, fiber content, fat content, color, flavor, taste and crispiness. The mixture of rice flour and tapioca had highly significant effect on moisture content, ash content, fiber content, fat content, flavor and crispiness. Interactions of the two factors had highly significant effect on moisture content, ash content, fiber content, fat content, flavor, taste and crispiness. The proportion of cinnamon leaf of 4% and the mixture of rice flour and tapioca of (62,5%:37,5%) produced the best quality of cinnamon leaf flavored crisp. . Key words : Cinnamon leaf flavored crisp, rice flour, tapioca